2021
DOI: 10.51628/001c.26985
|View full text |Cite
|
Sign up to set email alerts
|

Moving outside the lab: The viability of conducting sensorimotor learning studies online

Abstract: Collecting data online via crowdsourcing platforms has proven to be a very efficient way to recruit a large and diverse sample. Studies of motor learning, however, have been largely confined to the lab due to the need for special equipment to record movement kinematics and, as such, are typically only accessible to specific participants (e.g., college students).As a first foray to make motor learning studies accessible to a larger and more diverse audience, we developed an online, web-based platform (OnPoint) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(121 citation statements)
references
References 77 publications
13
101
2
Order By: Relevance
“…This proof-of-concept study thus showcases a powerful new approach to study motor learning in the wild, demonstrating in the context of motor learning research, the scientific value of data collected on a large scale in non-controlled conditions (also see: Tsay et al, 2021b). Limitations of this study included factors that were not considered such as Aim Lab tasks the player might have played, other than Gridshot, time of day of gameplay, or number of sessions contributing to a single day of player data.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This proof-of-concept study thus showcases a powerful new approach to study motor learning in the wild, demonstrating in the context of motor learning research, the scientific value of data collected on a large scale in non-controlled conditions (also see: Tsay et al, 2021b). Limitations of this study included factors that were not considered such as Aim Lab tasks the player might have played, other than Gridshot, time of day of gameplay, or number of sessions contributing to a single day of player data.…”
Section: Discussionmentioning
confidence: 79%
“…The future of studying motor learning through video games is promising (Anguera et al, 2013;Stafford and Dewar, 2014;Chen et al, Stafford and Vaci, 2021;Tsay et al, 2021b). Gaming provides a unique medium and potentially large data sets to investigate how motor skills are developed through intrinsic motivation, rather than financial incentive (Aung et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear mixed model (LMM) did not show effects of Mouse Type on single-trial learning (STL), although we observed that participants using a trackpad exhibited longer reaction times than others, consistent with a previous report. 43 Mouse position sampling rates depended on the exact hardware that each participant used to complete the task. Sampling rates were likely affected by features of the specific mouse used, along with features of the specific computer used, as computers may limit the rate at which the browser samples data in order to cope with limited processing power.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in error-based learning (e.g., sensorimotor adaptation), the weights are altered such that the same motor command will result in an output that should reduce the error. Critically, in both learning processes, behavioral changes attributed to alterations to the sensorimotor map are limited in magnitude (Avraham, Ryan Morehead, Kim, & Ivry, 2021;Bond & Taylor, 2015;Kim, Morehead, Parvin, Moazzezi, & Ivry, 2018;Morehead, Taylor, Parvin, & Ivry, 2017;Tsay, Avraham, et al, 2020;Tsay, Ivry, Lee, & Avraham, 2021;Tsay, Kim, Parvin, Stover, & Ivry, 2021;; instead, behavior changes are primarily attributed to changes in motor planning (e.g., strategic re-aiming) (McDougle, Ivry, & Taylor, 2016). This last point is relevant when considering the contribution of use-dependent learning to skill acquisition.…”
Section: Biases That Arise From Use-dependent Changes In Motor Executionmentioning
confidence: 99%